Interaction between glutathione S‐transferase variants, maternal smoking and childhood wheezing changes with age. Issue 5 (3rd June 2013) - Wu, Jiakai; Hankinson, Jenny; Kopec‐Harding, Kamilla; Custovic, Adnan; Simpson, Angela
Abstract: Background: Maternal smoking increases the risk of respiratory symptoms in children. Glutathione S‐transferases (GSTs) detoxify xenobiotics from tobacco smoke, and functional polymorphism in GST gene(s) could predispose children to the detrimental effects of maternal smoking. Our objective was to investigate interactions between GST variants and maternal smoking in relation to the development of wheezing during childhood and whether any such interaction changes with time. Methods: In a population‐based birth cohort, we assessed maternal smoking and current wheeze at five time points during the first 11 yr of life. DNA was genotyped for GSTP1, GSTM1 and GSTT1 (n = 807). Longitudinal analyses were performed using generalized estimating equations. Results: During early childhood, children whose mothers smoked were more likely to wheeze, with the strongest association observed at age 3 yr (p = 0.006). In a longitudinal model, children with GSTP1 AA and AG genotypes had significantly higher risk of wheeze compared with GG homozygotes. We observed a significant interaction between GSTP1 and maternal smoking where the risk of infantile wheezing was significantly increased in AA homozygotes, but only if their mothers smoked (OR 2.59, [1.08–6.21], pint  = 0.03). Furthermore, amongst AA carriers, there was a significant interaction between child's age and maternal smoking, with the effect of maternal smoking on the risk of wheeze significantly diminishing with age (pint  = 0.05); no such findings were observed for GSTM1 and GSTT1 . Conclusions: Children with AA genotype for GSTP1 are at increased risk of early‐life wheezing if their mothers smoke, but the effect of maternal smoking on wheezing diminishes with time.